Burden on caregivers of schizophrenia outpatients in Brazil: Relationship to symptomatology and functioning. (December 2022) - Di Sarno, Elaine; Napolitano, Isabel; Louzã, Mario Rodrigues
Background: To investigate the objective and subjective burden on caregivers of schizophrenia outpatients and their associations with sociodemographic factors, symptomatology, and functioning. Methods: This study included 60 schizophrenic outpatients aged 18 to 65 years who were clinically stable for at least 6 months, and 60 caregivers aged 18 to 80 years who were in contact with the patient for ⩾30 hours/week. The patients were assessed using a sociodemographic questionnaire, the Clinical Global Impression Scale for Schizophrenia (CGI-SCH), and the Personal and Social Performance scale (PSP). The caregivers were assessed using a sociodemographic questionnaire and the Family Burden Interview Schedule, Brazilian version (FBIS-BR). Results: The objective burden was positively correlated with CGI-SCH cognitive symptom scores ( p = .032) and number of hours spent weekly with the patient ( p = .028), and negatively correlated with PSP score ( r = −.346, p = .007). The subjective burden showed a negative correlation with age of disease onset ( r = −.338, p = .08). The independent variables included in the regression model were family income ( p = .005), PSP score ( p = .009), patient marital status ( p = .012), patient gender ( p = .046), and reception of financial benefit ( p = .027) for objective burden; and disease duration ( p = .045) and father/mother or sibling relationship ( p = .001) for subjective burden. The coefficient of determination ( R 2 ) of the linear regression model for objective burden was 39.4%; subjective burden, 21.6%. Conclusion: Caring for female, single patients with longer disease duration, more severe cognitive symptoms, impaired functioning, and more caregiving time required per week were associated with higher caregiver burden levels.